1999
DOI: 10.1038/sj.bjc.6690558
|View full text |Cite
|
Sign up to set email alerts
|

Low density lipoprotein and liposome mediated uptake and cytotoxic effect of N4-octadecyl-1-β-D-arabinofuranosylcytosine in Daudi lymphoma cells

Abstract: Summary Low density lipoprotein (LDL) receptor-mediated uptake and cytotoxic effects of N 4 -octadecyl-1-β-D-arabinofuranosylcytosine (NOAC) were studied in Daudi lymphoma cells. NOAC was either incorporated into LDL or liposomes to compare specific and unspecific uptake mechanisms. Binding of LDL to Daudi cells was not altered after NOAC incorporation (K D 60 nM). Binding of liposomal NOAC was not saturable with increasing concentrations. Specific binding of NOAC-LDL to Daudi cells was five times higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…33) Furthermore, it is possible that rhinacanthins transferred to serum lipoprotein effectively accumulated in tumor tissues, since lipoproteins, especially low density lipoproteins, are known to deliver hydrophobic materials to tumor cells. [33][34][35][36] In the present study, the results demonstrated for the first time that rhinacanthins-N, -Q and -C entrapped in liposomes showed antiproliferative activities against HeLaS3 cells: The activities were slightly higher than that of free drugs after 24-and 48-exposure. Corresponding to the in vitro data, these liposomal drugs effectively suppressed tumor growth and increased the survival of Meth-A sarcoma-bearing BALB/c mice.…”
Section: Fig 3 Antiproliferative Activities Of Liposomal Rhinacanthsupporting
confidence: 50%
“…33) Furthermore, it is possible that rhinacanthins transferred to serum lipoprotein effectively accumulated in tumor tissues, since lipoproteins, especially low density lipoproteins, are known to deliver hydrophobic materials to tumor cells. [33][34][35][36] In the present study, the results demonstrated for the first time that rhinacanthins-N, -Q and -C entrapped in liposomes showed antiproliferative activities against HeLaS3 cells: The activities were slightly higher than that of free drugs after 24-and 48-exposure. Corresponding to the in vitro data, these liposomal drugs effectively suppressed tumor growth and increased the survival of Meth-A sarcoma-bearing BALB/c mice.…”
Section: Fig 3 Antiproliferative Activities Of Liposomal Rhinacanthsupporting
confidence: 50%
“…MA), is being used clinically in photodynamic therapy for age-related macular degeneration (Ichikawa 2004). Verteporfin is transported in the plasma primarily by lipoproteins (especially low-density lipoproteins), are known to deliver hydrophobic materials to tumor cells (de Smidt et al 1993;Koller-Lucae et al 1999;Pan et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cancer cells benefit from loss of LDLR feedback regulation for their growth, it is possible to use this phenomenon in cancer therapy. Koller-Lucae et al 25 reported that an anti-cancer drug, N 4 -octadecyl-1-␤-D-arabinofuranosylcytosine, can be incorporated into LDL and taken up by lymphoma cells via the LDLR pathway. Because the normal cells express lower levels of LDLR than the cancer cells, especially after being feedback regulated by a high level of sterol, anti-cancer drugs carried by LDL may target more specifically and more efficiently FIGURE 3 -Cholesterol regulation of SREBP and LDLR expression.…”
Section: Ldl Increased Pge 2 Synthesis In Cancer Cellsmentioning
confidence: 99%